Palladium-Catalyzed Reactions of Allenes with 2-Iodobenzenesulfonamides: Simple Synthesis of Benzosultams under Green Conditions - Nagarjuna Reddy, M.; Kumara Swamy, K. C. (Synthesis, 2014)
A palladium-catalyzed reaction for the synthesis of benzosultams from allenes and 2-iodobenzenesulfonamides in poly(ethylene glycol) medium is described. This route is compared with a second method involving an internal Heck reaction of alkene-functionalized 2-iodobenzenesulfonamides. Key products were characterized by single-crystal X-ray crystallography.
Keywords: palladium; catalysis; allenes; sulfonamides; green chemistry